2011
DOI: 10.1139/f2011-023
|View full text |Cite
|
Sign up to set email alerts
|

Generation-scale movement patterns of cutthroat trout (Oncorhynchus clarkii pleuriticus) in a stream network

Abstract: Movements by stream fishes have long been the subject of study and controversy. Although much discussion has focused on what proportion of fish adopt mobility within particular life stages, a larger issue involves the lifetime movements of individuals. I evaluated movements of different sizes and ages of Colorado River cutthroat trout (Oncorhynchus clarkii pleuriticus) using a variety of sampling methods from 1996 to 2001 in a 40 km network of main-stem and tributary segments of the North Fork Little Snake Riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 87 publications
9
34
1
Order By: Relevance
“…Atlantic salmon ceased feeding at temperatures >24°C, and they moved to cooler streams during warm conditions (Cunjak et al 2005, Breau et al 2007, 2011. Our results suggest that Masu Salmon also seek thermal refugia in small streams during summer (see also Inoue et al 1997).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Atlantic salmon ceased feeding at temperatures >24°C, and they moved to cooler streams during warm conditions (Cunjak et al 2005, Breau et al 2007, 2011. Our results suggest that Masu Salmon also seek thermal refugia in small streams during summer (see also Inoue et al 1997).…”
Section: Discussionsupporting
confidence: 55%
“…A similar pattern has been observed for Margaritifera margaritifera (Young andWilliams 1984, Österling et al 2008), but this contrasts with mussel species in the family Unionidae that typically parasitize a lower percentage of the available host resource (Neves and Widlak 1988, McLain and Ross 2005, reviewed by Strayer 2008. The high prevalence of Margaritiferidae glochidia on hosts may be explained by their occurrence in very dense beds, their extraordinarily high fecundity (∼10 6 glochidia/adult; Bauer 1994, Kondo 2008, Haag 2012, and the synchronous release of glochidia (Young and Williams Table 2.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Gowan et al (1994) found, for example, that streamdwelling fish can move long distances when conditions in their present foraging location become sub-optimal relative to conditions at other locations in the same reach. Movement was shown to be required for reproduction, dispersing to new habitats, or avoiding adverse habitat or resource conditions (Bryant et al, 2009;Flecker et al, 2010;Young, 2011).…”
Section: Original Articlementioning
confidence: 99%
“…Gowan et al, 1994;Bryant et al, 2009;Flecker et al, 2010;Young, 2011), the number of studies on this topic has increased, however mainly in temperate regions (e.g. Schlosser, 1991).…”
Section: Original Articlementioning
confidence: 99%